Language impairment in children aged 5 and 8 years after antiepileptic drug exposure in utero – the Norwegian Mother and Child Cohort Study. (30th December 2019) - Husebye, E. S. N.; Gilhus, N. E.; Spigset, O.; Daltveit, A. K.; Bjørk, M. H.
Abstract : Background and purpose: The purpose was to examine the consequences of antiepileptic drug (AED) exposure during pregnancy on language abilities in children aged 5 and 8 years of mothers with epilepsy. Methods: The study population included children of mothers with and without epilepsy enrolled in the Norwegian Mother and Child Cohort Study 1999–2008. Mothers prospectively provided information on epilepsy diagnosis, AED use during pregnancy and the child's language abilities at age 5 and 8 years, in questionnaires with validated language screening tools. AED concentrations in gestation week 17–19 and in the umbilical cord were measured. Results: The study population included 346 AED‐exposed and 388 AED‐unexposed children of mothers with epilepsy, and 113 674 children of mothers without epilepsy. Mothers of 117 and 121 AED‐exposed children responded to the questionnaires at age 5 and 8 years, respectively. For AED‐exposed children, the adjusted odds ratio for language impairment was 1.6 [confidence interval (CI) 1.1–2.5, P = 0.03] at age 5 years and 2.0 (CI 1.4–3.0, P < 0.001) at age 8 years, compared to children of mothers without epilepsy. Children exposed to carbamazepine monotherapy had a significantly increased risk of language impairment compared to control children at age 8 years (adjusted odds ratio 3.8, CI 1.6–9.0, P = 0.002). Higher maternal valproate concentrations correlated with language impairment at age 5 years. Periconceptional folic acid supplement use protected against AED‐associated language impairment. Conclusion: Foetal AED exposure in utero is associated with an increased risk of language impairment in children aged 5 and 8 years of mothers with epilepsy. Periconceptional folic acid use had a protective effect on AED‐associated language impairment.